Մարտիրոս Սարյանի անձնական գրադարանը - Ղազարյան, Էմմա (Հայաստանի ազգային գրադարան)
The Saryan Museum has its own library, where the books authored by Martiros Saryan, books about Martyros Saryan, Saryan’s own acquisitions, and the books with the autographs of the poets are collected. The library gives a wonderful idea of the poet's life and creative work, his intention, his spiritual interests.
Keywords: Գրադարաններ; Կերպարվեստ